2019
DOI: 10.1161/strokeaha.119.024757
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Lateralization and Collateral Compensatory Mechanisms in Patients With Carotid Artery Stenosis

Abstract: Background and Purpose— Four-dimensional phase-contrast magnetic resonance imaging enables quantification of blood flow rate (BFR; mL/min) in multiple cerebral arteries simultaneously, making it a promising technique for hemodynamic investigation in patients with stroke. The aim of this study was to quantify the hemodynamic disturbance and the compensatory pattern of collateral flow in patients with symptomatic carotid stenosis. Methods— Thirty-eight patients (mean, 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 55 publications
6
58
0
Order By: Relevance
“…Our results are in agreement with those presented in previous reports such as Zarrinkoob et al ( 10 ) who studied hemodynamic disturbance and compensatory pattern of collateral flow in patients with symptomatic carotid stenosis by studying blood flow rates (BFR) with four-dimensional phase-contrast magnetic resonance imaging and found that the ACOM was the major collateral that contributed to BFR equalization in patients with carotid artery stenosis.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with those presented in previous reports such as Zarrinkoob et al ( 10 ) who studied hemodynamic disturbance and compensatory pattern of collateral flow in patients with symptomatic carotid stenosis by studying blood flow rates (BFR) with four-dimensional phase-contrast magnetic resonance imaging and found that the ACOM was the major collateral that contributed to BFR equalization in patients with carotid artery stenosis.…”
Section: Discussionsupporting
confidence: 93%
“…23 The other imaging parameters were: Label duration 1800 ms, 4 BGS pulses, segmented 3D GraSE readout (TE ¼ 7.4 ms, TR ¼ 4377 ms, a ¼ 90 , 16 slices, TSE factor 19, echo planar imaging (EPI) factor 7, acquisition voxel size 2.75 Â 2.75 Â 6.0 mm 3 ), three dynamics including a proton density weighted (PD-weighted) M 0 scan, and an acquisition time of 5:41 min. • BH-fMRI was performed according to Pillai et al 24 with five end-expiratory breath-holds of 15 33 and duplicate acquisition of the k-space center for motion correction, 37 as described previously 27 , which followed the ASFNR recommendations 38 and as described previously. 39 Contrast-enhanced angiography of the arteries of the neck and the aortic arch was also performed to exclude other relevant stenoses arteries that supply the brain.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Ipsilateral to the stenosis, we measured decreased CBF (-18% in iWSA-GM), which is in agreement with previous PET 52 and MRI studies 7,53 as well as the model of Powers et al 18 In the contralateral hemisphere, absolute CBF values were comparable to HCs, but the variability was increased (SD across subjects increased by þ22% in patients compared to HCs within iWSA-GM). This could be explained by subject specific collateralizations of blood flow, 15 that affect the contralateral hemisphere, and thereby increasing the inter-subject variability of contralateral CBF. Even though no obvious signs of arterial delay artefacts were found, CBF in watershed areas of ICAS-patients may potentially be affected by delayed blood arrival.…”
Section: Impaired Perfusion (Cbf Cvr and Rcbv)mentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated and comprehensive imaging assessment of intracranial vessels, including luminal stenosis, vessel wall, and blood flow conditions, is expected to be valuable for neurovascular disease diagnosis and to advance research. [1][2][3][4] MRI sequences are used to assess different aspects of vessel structure and blood flow. However, most existing sequences address only a single aspect of the conditions of intracranial vessels, and multiple sequences need to be performed to achieve a comprehensive assessment, which leads to prolonged total acquisition time and limits clinical application.…”
Section: Introductionmentioning
confidence: 99%